Комунікативні стратегії та тактики реалізації концептуальної опозиції «США–СХІД» у сучасному американському політичному дискурсі (на матеріалі промов Барака Обами за 2012–2013 рр.) - Пилипчук, Тетяна Володимирівна; Pylypchuk, T. V. (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті досліджено комунікативні стратегії та тактики реалізації концептуальної опозиції «США–СХІД» у сучасному американському політичному дискурсі. З’ясовано сутність і зміст таких понять, як політичний дискурс, концептуальна опозиція, комунікативна стратегія й тактика. На основі аналізу промов Барака Обами визначено та охарактеризовано основні стратегії й тактики побудови цієї концептуальної опозиції, а саме: стратегію групової ідентифікації та протиставлення. The article dwells on the notions of political discourse, communicative strategy and tactic. The author focuses attention on the strategies and tactics employed in contemporary American political discourse to render the conceptual opposition «USA-EAST». The results of the conducted research give reason to confirm that the conceptual opposition «USA-EAST» in Barack Obama’s speeches is rendered through the strategies of group identity and contrasting. The first strategy consists of such tactics as inclusion and distancing. Positive image of the United States of America, the country which protects not only its interests, but the interests of people of all nationalities and religions, is rendered through inclusion tactic. The separation of the United States of America from other countries is achieved by distancing tactic. The second strategy, the strategy of contrasting, compares both components of the given opposition, USA and EAST.
The Conceptual Opposition «USA–EAST» Through Communicative Strategies and Tactics in Contemporary American Political Discourse (оn the Materials of Barack Obama’s Speeches for 2012–2013 Years)
Keywords: політичний дискурс; political discourse; концептуальна опозиція; conceptual opposition; комунікативні стратегії та тактики; communicative strategies and tactics